The influence of breastfeeding on child development (Research, Society and Development, 2021)
Introduction: The research presents an assessment, based on bibliographic studies, on breastfeeding and its impact on child development. Objective: To verify the importance of breastfeeding for the child's development and the consequences of lack of it. Methodology: For the construction of the article, a literature review was used, based on research on scientific article sites, such as Scielo, PubMed, Government Agencies and Magazines, through a search for information relevant to the topic. Results and Discussion: We analyzed 50 references on the topic, the results found in the articles showed that babies breastfed on exclusive breastfeeding until 06 months of age had a better development than those breastfed until 04 months or even those who did not breastfeed in the first year of life. Conclusion: Exclusive breastfeeding is extremely important for the mother and her baby, this connection of breastfeeding protects the baby from respiratory infections, reducing the risk of allergies, and is related to the better motor development of the child, so it is essential that mothers are motivated to breastfeed their children, in view of the benefits mentioned above, among others.